Involvement of RBP-J interacting and tubulin-associated protein in the distribution of protein regulator of cytokinesis 1 in mitotic spindles - Caspers, Julia; Ritter, Andreas; Bahrami, Badi; Hoock, Samira Catharina; Roth, Susanne; Friemel, Alexandra; Oswald, Franz; Louwen, Frank; Kreis, Nina-Naomi; Yuan, Juping (Frontiers in Cell and Developmental Biology, 2025)
The protein regulator of cytokinesis 1 (PRC1) is a key regulator of microtubule crosslinking and bundling, which is crucial for spindle formation and cytokinesis. RITA, the RBP-J interacting and tubulin-associated protein, is a microtubule associated protein. We have reported that RITA localizes to mitotic spindles modulating microtubule dynamics and stability as well as to spindle poles affecting the activity of Aurora A. As defective chromosome congression and segregation are the most remarkable features of cells depleted of RITA, we aimed to explore further potential related mechanisms, using various cellular and molecular techniques, including clustered regularly interspaced short palindromic repeats technique/deactivated CRISPR-associated protein 9 (CRISPR/dCas9), mass spectrometry, confocal microscopy, immunofluorescence, immunoprecipitation and Western blot analysis. Here, we show that FLAG-RITA precipitates PRC1 and tubulin, and that these two proteins co-localize in the central region of the central spindle. Reduction of RITA enlarges the staining area of PRC1 in mitotic spindles as well as in the central spindle. Its suppression reduces the inter-centromere distance in metaphase cells. Interestingly, microtubule bundles of the central spindle are often less organized in a non-parallel pattern, as evidenced by increased angles, relative to corresponding separating chromosomes. These data suggest a novel role for RITA in mitotic distribution of PRC1 and that its deregulation may contribute to defective chromosome movement during mitosis. As both RITA and PRC1 are closely associated with malignant progression, further work is required to elucidate the detailed molecular mechanisms by which RITA acts as a modulator in central spindle formation and cytokinesis.